Prognostic significance of increased bone marrow microcirculation in newly diagnosed multiple myeloma: results of a prospective DCE-MRI study - Merz, Maximilian; Wagner, Barbara; Jauch, Anna; Hose, Dirk; Goldschmidt, Hartmut; Hillengaß, Jens (European radiology, 2016)
ObjectivesAim of this prospective study was to investigate prognostic significance of increased bone marrow microcirculation as detected by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for survival and local complications in patients with multiple myeloma (MM).MethodsWe performed DCE-MRI of the lumbar spine in 131 patients with newly diagnosed MM and analysed data according to the Brix model to acquire amplitude A and exchange rate constant k ep. In 61 patients a second MRI performed after therapy was evaluated to assess changes in vertebral height and identify vertebral fractures.ResultsCorrelation analysis revealed significant positive association between beta2-microglobulin as well as immunoparesis with DCE-MRI parameters A and k ep. Additionally, A was negatively correlated with haemoglobin levels and k ep was positively correlated with LDH levels. Higher baseline k ep values were associated with decreased vertebral height in a second MRI (P = 0.007) and A values were associated with new vertebral fractures in the lower lumbar spine (P = 0.03 for L4). Pre-existing lytic bone lesions or remission after therapy had no impact on the occurrence of vertebral fractures. Multivariate analysis revealed that amplitude A is an independent adverse risk factor for overall survival.ConclusionDCE-MRI is a non-invasive tool with significance for systemic prognosis and vertebral complications. Key Points • Qualitative parameters from DCE-MRI are correlated with established factors of disease activity • Increased marrow microcirculation might be a risk factor for loss of vertebral height and fractures • Amplitude A is an independent predictor for shortened overall survival
Published online: 29 July 2015
Gesehen am 30.10.2019